2011
DOI: 10.2174/138161211796150783
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole and Ropinirole Treatment for Cocaine Dependence: Evidence from a Pilot Study

Abstract: Our pilot study indicates that cocaine craving decreases with both aripiprazole and ropinirole treatment but aripiprazole is more efficacious in reducing cocaine use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 42 publications
1
14
0
1
Order By: Relevance
“…L-DOPA showed beneficial effects on the number of cocaine-negative urine samples, but only in combination with CM + CBT + VBRT, suggesting that L-DOPA pharmacotherapy may be an option for cocaine dependence when combined with behavioral therapies (Schmitz et al, 2008). Ropinirole acted as, albeit a weak, reinforcer in nonhuman primates (Freeman, Heal, McCreary, & Woolverton, 2012), which partly supports clinical data, suggesting that ropinirole marginally reduced craving in humans (Meini et al, 2012) and reduced the subjective intensity for the "cocaine rush" (Maremmani et al, 2011). Treatment with another dopamine D 2 agonist, pramipexole, caused perseverated responding in a reversal learning task, which was associated with stimulant dependence, rather than compulsive measures, suggesting additional efficacy for the potential treatment of SUD (Ersche et al, 2011).…”
Section: L-dopasupporting
confidence: 58%
“…L-DOPA showed beneficial effects on the number of cocaine-negative urine samples, but only in combination with CM + CBT + VBRT, suggesting that L-DOPA pharmacotherapy may be an option for cocaine dependence when combined with behavioral therapies (Schmitz et al, 2008). Ropinirole acted as, albeit a weak, reinforcer in nonhuman primates (Freeman, Heal, McCreary, & Woolverton, 2012), which partly supports clinical data, suggesting that ropinirole marginally reduced craving in humans (Meini et al, 2012) and reduced the subjective intensity for the "cocaine rush" (Maremmani et al, 2011). Treatment with another dopamine D 2 agonist, pramipexole, caused perseverated responding in a reversal learning task, which was associated with stimulant dependence, rather than compulsive measures, suggesting additional efficacy for the potential treatment of SUD (Ersche et al, 2011).…”
Section: L-dopasupporting
confidence: 58%
“…Recent reports demonstrate that ropinirole is able to reduce the subjective reinforcing effect of cocaine in humans [96], [97]; moreover Hoefer et al [51] showed that ropinirole was able to counteract the reward deficit in methamphetamine withdrawal in rats, supporting the hypothesis that activating, rather than blocking, the DAergic system could help attenuating drug seeking behaviour [98]. Additional studies need to be undertaken to evaluate ropinirole efficacy in alcohol relapse in order to suggest its administration as a pharmacological aid in controlling the chronic relapsing nature of alcohol abuse.…”
Section: Discussionmentioning
confidence: 99%
“…P = primary outcome; S = secondary outcome;* significant at P  < 0.05;** significant at P  < 0.01;*** significant at P  < 0.001;RaR = rate ratio; RR = relative risk; OR = odds ratio; MD = mean difference;Ω range of population SD reflects the CI of the expected effect size;α range of population SD based on opinion on a viable effect; a one‐directional relationship was assumed in all instances; Based on:a 31;b 32;c 33;d 34;e 35;f 36;g values specified in the sample size calculation;h 37;i 38;j 39;k 40;l 41;m 42;n 43;o 44;p 45;q 46;r 47;s 48;t 49;u 50;v 51;w 52;z 53;y values specified in the sample size calculation.HAMD = Hamilton Rating Scale for Depression; p.p.m. = parts per million.…”
Section: Methodsmentioning
confidence: 99%